Quality of Life Following Early Orthodontic Therapy for Anterior Crossbite: Report of Cases in Twin Boys - Eluza Piassi; Leonardo Santos Antunes; Marcia Rejane Thomas Canabarro Andrade; Lívia Azeredo Alves Antunes (Hindawi Limited, 2016)
Anterior crossbite (AC) refers to a condition in which the maxillary anterior teeth are placed lingually in their relationship with the mandibular anterior teeth. This dental condition results in visible incisor differences that are associated with higher levels of dissatisfaction with appearance and have potential to negatively impact on oral health-related quality of life (OHRQoL) of the children. The aim of this paper was to report two cases of interceptive orthodontic treatment of twin children with anterior crossbite and its impact on OHRQoL of these children. Although AC affects negatively psychosocial aspects of OHRQoL of the children, the interceptive orthodontic treatment of children with AC was essential to improve their OHRQoL.